Tools sustainability in buildings - Sena Neto, Plácido Gondim de; Alcântara, Roselene de Lucena (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The sector of the Brazilian civil construction grew at an accelerated rate. As a result, can be enumerated public and privateworks in preparing the country for the World Cup, which encouraged several changes related to environmental, economic and socio-cultural issue. Even with this growth, and the many positive impacts on society, the issue of environmental sustainability still has a large deficit by the absence of good environmental management, of government and some companies and also for a considerable part of the population. Guided by this question, the work addresses issues involving certain parameters of environmental sustainability in urban and residential environments, pointing sustainable building measures and main advantages. In this context, visits were made to the works constructed involving the issue of sustainability or who have used technologies and sustainable methods, maintaining environmental comfort, bringing savings and better use of renewable natural resources .It was demonstrated that the use of sustainable actions in residential, building environments and other public premises, can be considered a way to manage human activities so that the company fits your needs, planning and acting in order to conserve and preserve the equilibrium environmental, ensuring the maintenance of ecosystems.